(untitled) (Bangladesh Veterinarian, 2015)
Little is known of the occurrence of surgical affections of cattle at the government veterinary hospitals of Bangladesh. This study was undertaken to determine the occurrence of surgical disorders in five Upazila Veterinary Hospitals (UVH) in greater Pabna administrative district. A total of 33,584 sick animals were investigated and the overall occurrence of surgical disorders is 12.9%. The most common surgical affection is navel ill (25.8%) followed by myiasis (13.0%), foot diseases (11.3%), arthritis (8.8%) and teat obstruction (8.4%). Navel ill, umbilical hernia, arthritis, horn affections, urolithiasis and tail gangrene are more common in male than female. Foot diseases, myiasis, upward patellar fixation and hip dislocation are more common in female than male. Myiasis and arthritis are found more in summer, whereas foot diseases, urolithiasis and teat crack are more common in winter. DOI: http://dx.doi.org/10.3329/bvet.v31i1.22841 Bangl. vet. 2014. Vol. 31, No. 1, 38-45